(Carotenoids and Its Use in Industries) - Sudibyo, Agus (Warta Industri Hasil Pertanian, 1990)
Carotenoids are widely distributed in nature. They are found in plants, insects, birds, and other animals producing a wide array of brilliant yellow to red colors. This paper reviewed the structure of carotenoids, Their properties and their influence factors, production and application in industries.